2004
DOI: 10.1021/bp049841q
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of N-Acetylmannosamine (ManNAc) Analogue-Resistant Cell Lines as Improved Hosts for Sialic Acid Engineering Applications

Abstract: Metabolic substrate-based sialic acid engineering techniques, where exogenously supplied N-acetylmannosamine (ManNAc) analogues are utilized by the sialic acid biosynthetic pathway, allow the cell surface to be endowed with novel physical and chemical properties and show promise for increasing the quality of recombinant glycoproteins. The in vitro toxicity of many ManNAc analogues, however, hinders the large-scale adoption of this technology. In this study, we used a selection strategy where cells were subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Detection of Apoptosis by Annexin V Flow Cytometry AssaysThe Annexin V/propidium iodide flow cytometry method was used for the detection and quantification of apoptosis in transfected or GD3-treated HEK AD293 cells by following the procedure previously reported for Jurkat cells (39,40) with the added step of trypsinizing the adherent HEK cells (the previously tested Jurkat cells grow in suspension and did not require this step). After trypsinization and resuspension in complete medium, cells were counted with a Coulter Z2 instrument, and 1.0 ϫ 10 6 cells from each sample were pelleted by centrifugation, washed by gentle resuspension in Dulbecco's phosphate-FIGURE 1.…”
Section: Preparation and Transfection Of Short Hairpin Rnas (Shrnas) mentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of Apoptosis by Annexin V Flow Cytometry AssaysThe Annexin V/propidium iodide flow cytometry method was used for the detection and quantification of apoptosis in transfected or GD3-treated HEK AD293 cells by following the procedure previously reported for Jurkat cells (39,40) with the added step of trypsinizing the adherent HEK cells (the previously tested Jurkat cells grow in suspension and did not require this step). After trypsinization and resuspension in complete medium, cells were counted with a Coulter Z2 instrument, and 1.0 ϫ 10 6 cells from each sample were pelleted by centrifugation, washed by gentle resuspension in Dulbecco's phosphate-FIGURE 1.…”
Section: Preparation and Transfection Of Short Hairpin Rnas (Shrnas) mentioning
confidence: 99%
“…The full names and complete list of human sialyltransferases and pathway enzymes are given in Table 1. buffered saline, centrifuged again, and suspended in staining buffer. The cells were stained with fluorescein isothiocyanatelabeled Annexin V and propidium iodide and analyzed by flow cytometry as described (39,40).…”
Section: Preparation and Transfection Of Short Hairpin Rnas (Shrnas) mentioning
confidence: 99%
“…23,24 Some mannosamine analogues might not be recognized by these enzymes and, furthermore, several mannosamine analogues have been reported to be cytotoxic. 25,26 Sialic acid glycoengineering could become more efficient using unnatural sialic acids that can be directly incorporated into sialoglycans without extensive enzymatic conversion. So far, only a few unnatural sialic acid analogues have been developed, and data comparing the performance of these analogues with the corresponding mannosamine analogues in vitro and in vivo are scarce.…”
mentioning
confidence: 99%
“…In all cases, cell counts were compared with solvent-treated controls; in particular, because stock solutions of 1 were prepared in EtOH (to maintain sterility and assist solubility), the culture medium for all cell-based assays were adjusted to contain the same amount of ethanol as the test well with the highest level of 1 . It should be noted that this control was done simply as a precaution because the amount of EtOH used was less than 0.4 % (v/v), a level that previous studies have showed had no noticeable effect on the biological endpoints under evaluation [10, 20, 27]. …”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the sialic acid content was normalized against total protein concentration rather than against number of cells as is typically done in our experiments [7, 10, 27, 29]. Briefly, the cells from the harvested aliquots were washed with PBS to removed residual serum glycoprotein and re-suspended in PBS, lysed by freeze/thaw cycles, and centrifuged (16100 × g , 1.0 min).…”
Section: Methodsmentioning
confidence: 99%